GAMBARAN KEJADIAN PARTUS LAMA PADA IBU BERSALIN DI UPTD PUSKESMAS BATARAGURU KOTA BAUBAU TAHUN 2021-2025 - Nining Frianti; Haslina, Marwah Aisyah S; Wa Ode Maya Ghina Cahyani (JOMIS (Journal of Midwifery Science), 2026)
Prolonged labor remains a significant concern in maternal healthcare services as it may increase the risk of complications during childbirth for both mothers and newborns. This study was conducted to describe the incidence of prolonged labor among women giving birth at the Bataraguru Public Health Center, Baubau City, during the period of 2021–2025. A quantitative descriptive research design was employed in this study. The sample consisted of 118 delivering mothers selected using a total sampling technique, allowing all eligible members of the population to be included as respondents. Data were obtained from medical records and delivery registers available at the health facility. Data analysis was performed using univariate analysis and presented in the form of frequency distributions and percentages. The results showed that 76 respondents (64.4%) experienced normal labor, while 42 respondents (35.6%) experienced prolonged labor. The characteristics of mothers who experienced prolonged labor were predominantly found among those in high-risk age groups, namely younger than 20 years and older than 35 years, among primiparous and grand multiparous mothers, and among mothers who delivered infants with birth weights outside the normal range. It can be concluded that prolonged labor is still encountered among a proportion of delivering mothers at the Bataraguru Public Health Center, Baubau City. Therefore, improving the quality of antenatal care through early identification of risk factors and continuous monitoring of labor progress is essential to minimize maternal and neonatal complications.